Faktor Yang Mempengaruhi Capital Structure Pada Sektor Industri Dasar Dan Kimia - Thio Lie Sha (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
The purpose of this study is to obtain empirical evidence about the effects of business risk, profitability, firm size, asset structure, and growth of asset to capital structure in the company's manufacturing base and chemical industry sectors listed on the Indonesia Stock Exchange during 2011-2014. The total sample is 80 samples obtained by the purposive sampling method. Data analysis was done using the multiple linear regression method with SPSS software 20 version. The result based on the t-test indicate that business risk, firm size, asset structure, and asset growth of the company has a positive and significant influence on structure capital., profitability has a negative and significant influence on structure capital. F-test results showed that the variable business risk, profitability, firm size, asset structure and asset growth together have a significant effect on the capital structure.